PENGEMBANGAN DESAIN PEMBELAJARAN BERBASIS MASALAH BERBANTUAN WORDWALL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SD - Silvi; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Study employs a Research and Development (R&D) design using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The purpose of this research is to develop a Problem-Based Learning (PBL) design assisted by Wordwall media and to determine its effectiveness in improving the mathematical problem-solving skills of fifth-grade elementary school students, specifically on the topic of simple fractions. The research instruments include validation sheets from material and media experts, mathematical problem-solving skill tests, observation sheets, and student response questionnaires. Data collection techniques were conducted through observation, testing, and questionnaires. Data analysis techniques included qualitative descriptive analysis for validation and observation data, as well as quantitative descriptive analysis for test and questionnaire data, including the calculation of the N-Gain score to measure the improvement in students' problem-solving skills. The results showed an increase in the students' average score from 72.14 in the pretest to 90.71 in the posttest, with an N-Gain value of 0.69, categorized as